JIHAD BUKAN HANYA PERANG SUCI: Telaahan Teoritik Terhadap Ayat-Ayat Jihad dalam Al-Quran - Sefriyono Sefriyono (Turast: Jurnal Penelitian dan Pengabdian, 2021)
Of the 114 surahs in the Qur'an, there are 24 surahs with 164 verses that talk about jihad in various variations of words. Of the 164 verses, there are 22 verses that have the potential for acts of violence if understood literally and coupled with the dominance of qital words in these verses. The qital verses are said to have been revealed more in the Medina period, when compared to the Mecca period, which talked a lot about self-control. The dynamics of the Muslims at that time also contributed to the change in the terminology of jihad. Jihad is not only defined by war or acts of violence. The invitation of parents to polytheism, for example, as contained in chapter 29 paragraph 8 and letter 31 paragraph 15 does not have to be fought with violence. This verse even continues to recommend to continue to do good to the parents in question. In other Surahs such as Sura 45 verse 15 there is also a recommendation with wealth, not carrying weapons. This has given rise to various forms of meaning about jihad, such as greater jihad (al-jihad al-akbar)—the struggle against self and lesser jihad (al-jihad al-asghar)—fighting those who are hostile to the way of Allah. On the one hand, jihad can also be interpreted in an esoteric way—mujahadah, namely a genuine effort to draw closer to Allah, on the other hand, it can also be interpreted exoteric—the holy war.